Phthalate esters in municipal sewage treatment plants: occurrence level, removal rate and optimum combination technology - Zheng, Xiqiang; Lu, Guanghua; Liu, Jianchao; Jiang, Runren (Frontiers in Environmental Engineering, 2023)
The concentrations, and removal rates of five phthalate esters (PAEs) (dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), diisobutyl phthalate (DiBP) and di (2-ethylhexyl) phthalate (DEHP)) in the five representative sewage treatment plants of Chaohu catchment were investigated by season in this study. Our results showed that five PAEs were ubiquitous contaminants in the five sewage treatment plants. Thereinto, the contents of DiBP were significantly higher than that of the other four kinds of PAEs, and the total concentrations of PAEs in the influents in summer (17.51–33.93 μg L−1) were significantly higher than those in winter (10.14–24.08 μg L−1). Different PAEs showed different removal efficiencies in sewage treatment plants, and the orders of individual removal rates was as follows: DMP > DEP > DBP > DiBP > DEHP. The total concentration of PAEs in the effluent was relatively low in Chaohu catchment. The biochemical treatment section of the sewage treatment plant contributed the most to the removal of total PAEs, while the pretreatment and advanced treatment sections contributed less. In addition, environmental temperature had an obvious effect on the biochemical treatment process. Appropriate combined treatment processes could efficiently improve the removal effect of PAEs in sewage treatment plants.